1988
DOI: 10.1037/0033-2909.104.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Relapse after recovery from unipolar depression: A critical review.

Abstract: Studies of relapse after recovery from unipolar depression are reviewed. Methodological deficiencies identified include (a) inadequate definitions of recovery and relapse; (b) incomplete descriptions of the samples; (c) inadequate inclusion and exclusion criteria; and (d) inadequate data analyses that do not take into account the changing composition of samples over follow-up. Despite the methodological problems, it is tentatively concluded that relapse after recovery from unipolar depression is frequent but l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
190
0
7

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 301 publications
(204 citation statements)
references
References 66 publications
(148 reference statements)
7
190
0
7
Order By: Relevance
“…Several researchers have found that an increased Hamilton score, reflecting the presence of a large number of symptoms and/or several severe symptoms, predicts recurrent episodes in adult inpatient samples (e.g., Belsher & Costello, 1988;O'Leary et al, 2000;Ramana et al, 1995). However, there have been a few exceptions, including two studies of children and adolescents which found that severity of depression, as indicated by an extracted Hamilton score, does not predict later recurrent episodes (Birmaher et al, 2004;Rao et al, 1995).…”
Section: Severity Of First/index Episodementioning
confidence: 99%
See 4 more Smart Citations
“…Several researchers have found that an increased Hamilton score, reflecting the presence of a large number of symptoms and/or several severe symptoms, predicts recurrent episodes in adult inpatient samples (e.g., Belsher & Costello, 1988;O'Leary et al, 2000;Ramana et al, 1995). However, there have been a few exceptions, including two studies of children and adolescents which found that severity of depression, as indicated by an extracted Hamilton score, does not predict later recurrent episodes (Birmaher et al, 2004;Rao et al, 1995).…”
Section: Severity Of First/index Episodementioning
confidence: 99%
“…The importance of adult SLEs has been highlighted in many other studies (Belsher & Costello, 1988). For example, one study followed 67 individuals with recurrent depression following successful treatment for depression (i.e., psychotherapy and/or medication).…”
Section: Stressful Life Events (Sles)mentioning
confidence: 99%
See 3 more Smart Citations